Development of a Water Resources Distribution and Management Tool (SPEHR); Applied - Lemaitre Ruiz, Ximena; Corzo, Gerald Augusto; Angarita, Hector Andres; Santos Granados, Germán Ricardo (Ed. Easy Chair Publications, 2018)
Water management is a complex problem that relates to human and physical variables that are very hard to predict, there is a cultural and social and human driven variables (Agricultural practices, Cities growth and others) that are hard to capture into the complex interactions of the water allocation and the hydrological system. This research presents a new novel yet simple system that integrates information from river basin social and hydrological variables in an online system for decision support. The concept developed so far represents the Magdalena river system in Colombia, and allows to simulate and to share ideas. A communication bar includes a score of goodness provided by decision makers such that a level of agreement between actors can be achieved. Aside of this, the system is made open source such that other river basin can be set up and even other hydrological modelling systems can be plugged in.

La gestión del agua es un problema complejo que se relaciona con variables humanas y físicas que son muy difíciles de predecir, hay variables culturales y sociales y humanas (prácticas agrícolas, crecimiento de las ciudades y otras) que son difíciles de captar en las complejas interacciones de la asignación del agua y el sistema hidrológico. Esta investigación presenta un nuevo y sencillo sistema que integra la información de las variables sociales e hidrológicas de la cuenca hidrográfica en un sistema en línea de apoyo a la toma de decisiones. El concepto desarrollado hasta ahora representa el sistema del río Magdalena en Colombia, y permite simular y compartir ideas. Una barra de comunicación incluye una puntuación de bondad proporcionada por los responsables de la toma de decisiones, de manera que se pueda alcanzar un nivel de acuerdo entre los actores. Además, el sistema es de código abierto, por lo que se pueden crear otras cuencas hidrográficas e incluso conectar otros sistemas de modelización hidrológica.
Development of a Water Resources Distribution and Management Tool (SPEHR); Applied
Keywords: Sistemas hídricos sostenibles; Escasez de agua; Demanda de agua; Almacenamiento; Irrigation; Storage; Sustainability water systems; water allocation; Water Demands; water scarcity; Riego; Almacenamiento; Sistemas hídricos sostenibles; Asignación de agua; Demanda de agua; Escasez de agua